Upaya Pengembangan Promosi Wisata Budaya dengan Aspek 4A di Situs Percandian Batujaya Kab. Karawang Prov. Jawa Barat - Widjaja, Hinijati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The Batujaya Temple site has the potential to attract both tangible (tangible) and intangible (intangible) attractions. So, it has a big opportunity to attract domestic and foreign tourists. To achieve this goal, a tourism strategy is needed in developing promotions on the site so that it resonates more and attracts tourists coming from various regions throughout Indonesia and abroad. The problem arises from the existence of a site that is only known to a limited number of local people around the site who live there, so that people who come from the community are limited, whereas with the discovery of a high value site, the existence of the site needs to be known and echoed throughout the world and known to the wider community. The aim of this research is to increase the number of people visiting the site. This research is an exploratory qualitative description, discussing tourism development at the Batujaya Temple Site in West Karawang. The data collection methods used consisted of: field observation, interviews, and literature study. The results of the research are the composition of strategic efforts consisting of the development of the 4A concept and sourced from field analysis: (1) Development of cultural tourism through social media, (2) Development of infrastructure, namely accessibility such as special transportation, directions, (3) Development of accessibility aspects, and (4) service amenities such as services such as homestays, information and security centers, craft centers. So that the goal of developing and increasing the cultural tourism attraction at the Batujaya Temple Site will be achieved for all domestic and foreign tourists.